Organizational Effects of Estrogens and Androgens on Estrogen and Androgen Receptor Expression in Pituitary and Adrenal Glands in Adult Male and Female Rats - Lagunas, Natalia; Fernández-García, José Manuel; Blanco, Noemí; Ballesta, Antonio; Carrillo, Beatriz; Arevalo, Maria-Angeles; Collado, Paloma; Pinos, Helena; Grassi, Daniela (Frontiers in Neuroanatomy, 2022)
Sex steroid hormones, such as androgens and estrogens, are known to exert organizational action at perinatal periods and activational effects during adulthood on the brain and peripheral tissues. These organizational effects are essential for the establishment of biological axes responsible for regulating behaviors, such as reproduction, stress, and emotional responses. Estradiol (E2), testosterone, and their metabolites exert their biological action through genomic and non-genomic mechanisms, bounding to canonical receptors, such as estrogen receptor (ER)α, ERβ, and androgen receptor (AR) or membrane receptors, such as the G protein-coupled estrogen receptor (GPER), respectively. Expression of ERs and AR was found to be different between males and females both in the brain and peripheral tissues, suggesting a sex-dependent regulation of their expression and function. Therefore, studying the ERs and AR distribution and expression levels is key to understand the central and peripheral role of sex steroids in the establishment of sex-specific behaviors in males and females. We investigated the organizational effects of estrogens and androgens in the pituitary and adrenal glands of adult male and female rats. For this, selective blockade of AR with flutamide or 5α-reductase with finasteride or aromatase with letrozole during the first 5 days of life has been performed in male and female pups and then quantification of ERs and AR expression in both glands has been carried out in adulthood. Data show that inhibition of dihydrotestosterone (DHT) and E2 production during the first five postnatal days mainly decreases the ER expression in male to female values and AR expression in female to male levels in the pituitary gland and increases AR expression in female to male levels in the adrenal gland. In contrast, blocking the action of androgens differentially modulates the ERs in males and females and decreases AR in both males and females in both glands. Altogether, the results suggest that neonatal modifications of the androgen and estrogen pathways can potentially lead to permanent modifications of the neuroendocrine functions of the pituitary and adrenal glands in the adulthood of both sexes.